Development expenditures towards firm's turnover and firm's market valuation: Evidence from Portugal and Spain - Lopes, I. T. (9th International Conference for Entrepreneurship, Innovation and Regional Development (ICEIRD 2016) - Responsible entrepreneurship. Vision, development and ethics, 2016)
Countries and firms became a very heavy spender on R&D and on education and training with an increasingly focus based on innovation. It is associated to changes by introducing new methods, ideas, or products. It also translates the ability to produce and transform knowledge, contributing to potential economic inflows. The current research, in the scope of business enterprise R&D intensity policy and European Union strategy 2020, aims to identify whether development expenditures in business enterprises have a significant impact on Portuguese and Spanish firms' economic returns and firm's market valuation, as well as to provide an overview on the convergence with European innovation strategy. Based on 68 Iberian non-financial listed companies, all of them with active development projects on innovation, an econometric framework was regressed. Without convergent R&D main funding source and national targeting rates, Portugal and Spain are significantly aligned on the impact of development expenditures on firm's turnover and on firm's market valuation. If managed together, firms can generate high value-added flows, from those innovative intangible resources.